Axial behavior of reinforced concrete column with ultra-high performance concrete stay-in-place formwork. (1st May 2020) - Tian, Huiwen; Zhou, Zhen; Zhang, Yi; Wei, Yang
Highlights: UHPC stay-in-place formwork is a promising alternative to traditional formwork system. An experimental study on the proposed composite columns is presented. Failure modes and key characteristics of axial load–strain relationships are discussed. Effects of type and number of grid layers and thickness of UHPC formwork are investigated. A finite element model for the composite columns is developed. Abstract: This paper presents the experimental and numerical study on the axial compressive behavior of a novel composite column that consists of a prefabricated grid-reinforced ultra-high performance concrete (UHPC) stay-in-place (SIP) formwork and post-cast concrete. Eight specimens, including six composite columns and two reinforced concrete columns were tested. The test variables included the type and number of grid layers as well as the thickness of UHPC formwork. According to the test results, the composite columns showed both higher axial load carrying capacity and elastic modulus, whereas the brittle nature of UHPC caused a decrease in ductility and toughness. The use of carbon fiber reinforced polymer (CFRP) grid could provide a more sufficient lateral confinement than stainless steel (SS) grid to achieve a strain hardening behavior and thus increased the ductility and toughness of the specimens. The use of more layers of SS grids could also have a positive effects on brittleness reduction. Furthermore, an analytical model was developed using a finite element (FE) program to simulate axial compressive response of the column. The whole failure process of the composite column and almost all the key characteristics of the load-strain curves were reasonably captured, and a good agreement was found between the calculated and measured load-strain curves, indicating the capability of the proposed FE model to predict the axial compressive behavior of the composite columns.